Similarity measure exercise for classification trees based on the classification path - Hasan Norsida, Adam M. B., Mustapha N., Abu Bakar M. R. (N/A, 2012)
Similarity measure exercise for classification trees based on the classification path by Hasan Norsida, Adam M. B., Mustapha N., Abu Bakar M. R.,